Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Explore thousands of questions and answers from a knowledgeable community of experts ready to help you find solutions. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

6x squared plus 12x plus 13 equals 2x squared plus 4

Sagot :

[tex]12x^2+12x+3=2x^2+4\\\\12x^2-2x^2+12x+3-4=0\\\\10x^2+12x-1=0\\\\a=10;\ b=12;\ c=-1\\\\\Delta=12^2-4\cdot10\cdot(-1)=144+40=184\\\\x_1=\frac{-b-\sqrt\Delta}{2a};\ x_2=\frac{-b+\sqrt\Delta}{2a}\\\\\sqrt\Delta=\sqrt{184}=\sqrt{4\cdot46}=2\sqrt{46}\\\\x_1=\frac{-12-2\sqrt{46}}{2\cdot10}=\frac{-6-\sqrt{46}}{10};\ x_2=\frac{-12+2\sqrt{46}}{2\cdot10}=\frac{-6+\sqrt{46}}{10}[/tex]